PERBANDINGAN KUALITAS HIDUP PASIEN KANKER PAYUDARA DENGAN KANKER SERVIKS YANG MENJALANI KEMOTERAPI DI RSUP FATMAWATI JAKARTA - Jesica Rachel Meliala (2021)
Breast cancer is cancer with slow growth in the breast and generally associated with hormonal, genetic, environmental, and lifestyle factors. Cervical cancer grows on the cervix that caused by HPV virus. Quality of life assessments can provide different prognostic information and the outcome on symptoms succeeds in predicting the survival for various types of cancer. This research was carried out to compare the quality of life of breast cancer patients with cervical cancer patients undergoing chemotherapy at Fatmawati Hospital, Jakarta. The method used is a cross-sectional design with accidental sampling technique and the number of samples in the study were 15 breast cancer patients and 15 cervical cancer patients. The Indonesian version of the EORTC QLQ C30 is used for measuring the quality of life of patients and analyze the comparison using simple linear regression calculations. The results of the study showed p=0,481 for general health scale, p=0,710 for functional scale, and p=0,093 for symptom scale. The conclusion obtained is that there is no difference in the quality of life of the two cancers. However, seen from the average score per domain, there is a slight difference in the physical and symptom domains